The Effectiveness of Coughing Effectively for Removing Secretions In Clients of Bronchial Asthma : Case study - Andan Firmansyah; Shofi Nurwahidah; Dadi Hamdani; Ade Fitriani; Asep Gunawan (HealthCare Nursing Journal, 2023)
Bronchial asthma is a chronic inflammatory disease that causes swelling and narrowing of the airways, causing increased hyperreactivity and airway hyperresponsiveness. The purpose of this case study is to gain real experience in providing direct nursing care to children suffering from bronchial asthma with a diagnosis of ineffective airway clearance. The method used by the author is descriptive analysis method in the form of case studies, with reports of nursing care through the nursing process approach. Subjects in children with bronchial asthma with ineffective airway clearance problems. Meanwhile, the data collection includes interviews, observations, physical examinations and documentation studies. The results of the case study at the assessment stage revealed that the client complained of shortness of breath accompanied by coughing up phlegm. The intervention and implementation used to overcome the accumulation of secretions is to practice effective coughing techniques which are carried out once a day. The conclusion of virginity care for children with bronchial asthma with ineffective airway clearance is partially resolved. Giving effective cough intervention is very efficient in removing secretions with the secretions being successfully removed.